Family therapy and schizophrenia: a brief theoretical overview and a framework for clinical practice. (15th June 2018) - Burbach, Frank R.
SUMMARY: Family or systemic therapy is often contrasted with psychoeducational approaches, but their historical differences have become blurred with the increasing development of integrated family interventions for psychosis. This article describes the theoretical context for the development of integrated family interventions and provides a framework for practice. It presents a collaborative, resource-oriented integrated family intervention for working with families and wider support networks within seven phases: the sharing of information and provision of emotional and practical support; identification of patient, family and wider network resources; encouraging mutual understanding; identification and alteration of unhelpful patterns of interaction; improving stress management, communication and problem-solving skills; coping with symptoms and relapse prevention planning; ending and ensuring that each session is a mini-intervention. It also includes guidelines for family intervention practice, as well as ideas for service development. LEARNING OBJECTIVES: Understand the theoretical developments in the field Be able to apply the integrated framework to family intervention in practice Consider different ways of developing family-based services DECLARATION OF INTEREST: None.